Spain’s Hesitation at the Gates of a COVID-19 Vaccine - Hans Eguia; Franco Vinciarelli; Marina Bosque-Prous; Troels Kristensen; Francesc Saigí-Rubió (Vaccines, 2021)
(1) Background: This study aims to delineate a pattern on vaccine hesitancy in a sample of the Spanish population, considering age groups and status as healthcare workers. (2) Methods: Participants were recruited using Twitter® as a dissemination tool to reach as many respondents as possible in different parts of the Spanish territory. The participants were recruited in a cross-sectional study, which included answering an online questionnaire. Data were collected from 10 September through 23 November 2020. Respondents answered questions asking whether they intended to be vaccinated and provided the main reason for their answers. To estimate associations between vaccination hesitancy and independent variables, we fit Poisson regression models with robust variance. (3) Results: One thousand and two responses were obtained, of which only 731 were validated. One hundred and sixty-four participants stated that they would not be vaccinated (22.43%), of which 20–24% were non-health workers or unemployed, 17.5% physicians, 31.5% other health workers, and almost 35% nurses. Concerns about lack of effectiveness of the vaccination, lack of safety when vaccinating and possibly dangerous adverse effects were the main causes provided. (4) Conclusions: This study indicates that more interventions are needed to achieve better communication with the population and health professionals. Receptiveness to the message of the importance and security of the COVID-19 vaccination could be an important strategy for improving these results.